Relevansi Nilai Informasi Akuntansi dan Informasi Intellectual Capital pada Perusahaan Berbasis Pengetahuan di Indonesia - Kusuma, Poppy Dian Indira (Jurnal Akuntansi dan Governance Andalas, 2020)
Financial accounting research has been questioning if the accounting information contained in financial statements has lost its relevance in the capital market. In addition, this study aims to examine the value relevance of accounting and intellectual capital information of knowledge-based companies in Indonesia. Data were taken from the sample of twenty-nine companies which were purposively selected from MAKE (Most Admirable Knowledge Enterprises) award nominee companies within 2014-2018. Using multiple regression linier analysis, the results show that accounting information and intellectual capital information have value relevance. Companies with higher earning per share, book value per share, as the proxies of accounting information, and intellectual capital have higher share price. These results imply the importance for companies to properly manage their assets and to invest more in intellectual capital to create value.